2009
DOI: 10.1021/es8034126
|View full text |Cite
|
Sign up to set email alerts
|

Using Oxygen Isotopes of Phosphate To Trace Phosphorus Sources and Cycling in Lake Erie

Abstract: Water samples collected during three sampling trips to Lake Erie displayed oxygen isotopic values of dissolved phosphate (delta18Op) that were largely out of equilibrium with ambient conditions, indicating that source signatures may be discerned. delta18Op, values in the Lake ranged from +10% per hundred to +17% per hundred, whereas the equilibrium value was expected to be around +14% per hundred. The riverine weighted average delta18Op, value was +11% per hundred and may represent one source of phosphate to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 22 publications
0
74
1
Order By: Relevance
“…In the western basin of Lake Erie, it has been suggested that internal P loading is an important source of P (Elsbury et al 2009), with implications for the increase in cyanobacterial blooms (Michalak et al 2013). Matisoff et al (2016) utilized eight different approaches to estimate internal P loading and reported mean year-round aerobic internal P loads (L net and L gross ) ranging from 157 to 332 mg SRP·m −2 ·year −1 (depending on estimation method).…”
Section: Lake Eriementioning
confidence: 99%
“…In the western basin of Lake Erie, it has been suggested that internal P loading is an important source of P (Elsbury et al 2009), with implications for the increase in cyanobacterial blooms (Michalak et al 2013). Matisoff et al (2016) utilized eight different approaches to estimate internal P loading and reported mean year-round aerobic internal P loads (L net and L gross ) ranging from 157 to 332 mg SRP·m −2 ·year −1 (depending on estimation method).…”
Section: Lake Eriementioning
confidence: 99%
“…Thus, a slight negative excursion of d 18 O p values of authigenic phosphate at this site most likely results from the higher rate of organic matter mineralization and hydrolysis of organophosphorus compounds, with subsequent turnover to re-equilibrate the phosphate with ambient water. In fact, non-equilibrium isotopic compositions of dissolved phosphate are found in many natural environments such as in ocean water below the euphotic zone (Colman et al, 2005) and lake water (Elsbury et al, 2009). Authigenic phosphate precipitated from DIP derived from hydrolysis of P org will have d 18 O p values out of equilibrium with ambient water and temperature conditions.…”
Section: O P Values Of Authigenic Phosphates In Zones Of Intensementioning
confidence: 99%
“…On the other hand, under abiotic conditions and at most earth-surface temperatures (<80°C) and pressures, phosphate resists O-isotope exchange (Lecuyer et al, 1999). With this distinction between biotic and abiotic environments, d 18 O P values can be used as a tracer to identify the sources and cycling of P in different environments including marine and freshwater systems (Paytan et al, 2002;Colman et al, 2005;Blake et al, 2005;McLaughlin et al, 2006;Elsbury et al, 2009). Furthermore, d 18 O P values of phosphate are a more reliable proxy than other oxyanions because: (a) unlike carbonates, in the absence of biological mediation, dissolved inorganic phosphate resists O-isotope exchange with water at temperatures and pH of most ecosystems (O'Neil et al, 2003;Zazzo et al, 2004); (b) Unlike sulfates, dissolved phosphate resists exchange with water at extreme pH during sample processing in the laboratory (as high as 10 M HNO 3 and $8.5 M NH 4 OH); and (c) phosphate in the form of mineral apatite is also more resistant to isotopic exchange relative to carbonates (Fortier and Luttge, 1995;Zazzo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The use of isotopic characterisation (i.e. δ 18 O-PO 4 ) would potentially aid the understanding of different sources of P and the importance of biological mediation and cycling in the hyporheic zone (Elsbury et al 2009;McLaughlin et al 2006). …”
Section: Discussionmentioning
confidence: 99%